Supporting students’ dance complementary training: Needs and challenges from the perspective of dance teacher students - Lojander, Tove (2020)
Dance complementary training (DCT) has become an essential part of every dancer´s basic training to address gaps in continuous training. Today we have access to many research results that suggest the value and benefit of DCT. In the current dance teacher program at Luleå University of Technology, DCT is included in one obligatory course module during the second-year studies. During the summer break and theoretical study periods, dance teacher students are supposed to continue their training on their own. As the lack of continuous and effective training can result in slower progression in dancing skills and increase the risk for injuries, it would be important that dance students avoid gaps in continuous training. In the context of this study, the main interest is to understand the needs and challenges dance teacher students have when practicing DCT, in order to help them with their self-training. Data was collected in the form of questionnaires, workshops with field observations, intervention and interviews. Relevant background research on motivation, self-regulation techniques and how to support autonomous motivation and self-regulation, has been conducted to support the discussion and conclusions of this thesis. The findings in this study suggest that students should get support in creating, organizing and planning their self-training. Feeling competent in self-training and when creating own exercises was important as it strengthened students’ autonomy. This suggests that the feeling of competence should be supported by autonomy supportive teaching strategies and by offering enough knowledge of DCT early in the program. When combining all the findings in this study, a need for a structure for DCT can be observed. Dance complementary training should be incorporated in the program from the start and have an ongoing status throughout the 5-year program. This study gives a suggestion of a model to support dance teacher students’ dance complementary training at Luleå University of Technology. Findings from this study can be utilized also by other dance education institutions when supporting dance students’ self-training and DCT.